La responsabilità penale del medico in relazione all’omessa diagnosi differenziale - Ascani, Cecilia (Cultura giuridica e diritto vivente, 2017)
The criminal liability of the physician in relation to the failure differential diagnosis] Integrates the offense of manslaughter the conduct of the doctor who, in the presence of a suitable symptoms to pose a differential diagnosis, fails to execute or carry out checks and investigations dutiful purpose of a correct formulation of the prognosis remaining, however, in the mistaken initial diagnostics position. Neither it will apply the limitation of liability for slight negligence, provided for in article 3 d.l. 13th September 2012, n. 158 (law 8th November 2012, n. 189), where the conduct of the physician prove unequal than the "best practices" would have required to do in this case. In the decision under review, the Court deals with many issues already beaten in the field of medical liability, namely the criteria to be followed in cases where the care of the patient follow each different parties operating a health workers, the diagnostic relevance of the error, omission offense and assessment causal link with the death event, as well as profiles of culpable responsibility in the medical field as a result of the introduction of law number 189 of 2012 or Law Balduzzi, as well as the latest Law Gelli-Bianco.